2023
DOI: 10.3390/antiox12040888
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Water Extraction of Rosmarinic Acid from Lemon Balm (Melissa officinalis L.) and Its Effect on Plant Cell Wall Constituents

Abstract: Rosmarinic acid (RA), an ester of caffeic acid and 3,4-dihydroxyphenyllactic acid, is a potent radical scavenger, a chelator of prooxidant ions, and an inhibitor of lipid peroxidation. RA-containing extracts are widely used natural antioxidants in food products, and many herbal preparations and food supplements, containing RA, are marketed with claims of beneficial health effects. The current study investigated the effectiveness of subcritical water extraction (SWE) for the recovery of RA from lemon balm (Meli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…extraction methods can be employed to assist polysaccharide extraction more fully, especially of the uronic acid-containing one. A good example of this is our very recent study on subcritical water extraction, which found that the yields of lemon-balm extracts and polysaccharides increased significantly with an increase in temperature and duration [21]. In fact, a detailed study on how subcritical water affects the yield and composition of echinacea extracts is being undertaken by us.…”
Section: Discussionmentioning
confidence: 98%
“…extraction methods can be employed to assist polysaccharide extraction more fully, especially of the uronic acid-containing one. A good example of this is our very recent study on subcritical water extraction, which found that the yields of lemon-balm extracts and polysaccharides increased significantly with an increase in temperature and duration [21]. In fact, a detailed study on how subcritical water affects the yield and composition of echinacea extracts is being undertaken by us.…”
Section: Discussionmentioning
confidence: 98%
“…Nastić et al (2018b) [40] reported higher DPPH values for SWE extract in the range of 60-160 • C while significantly lower antioxidant capacity was observed at 180 • C, which may be due to the degradation of antioxidants via pyrolysis. Since there is not always a positive correlation between the antioxidant capacity results and the individually recovered phenolic compounds when SWE is applied [43,44], the hydrolysis of phenolic compounds under the influence of specific SWE conditions could lead to the formation of Maillard products, whose radical scavenging properties are preserved [45].…”
Section: Determination Of Tpc and Acmentioning
confidence: 99%
“…The presence of an outer membrane in Gram-negative bacteria impairs the diffusion through the membrane The numerous studies conducted with plant extracts and essential oils containing various biologically active substances have shown effective results in controlling the colonial growth of pathogenic microorganisms. For example, rosmarinic acid-containing extracts have been widely investigated as natural antioxidants and biopreservatives in food products [35]. Similarly, eugenol has been found to play an important role in the inhibition of L. monocytogenes in meat [36].…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%